Role of Tumor Necrosis Factor in Tuberculosis - Fedor D. Kireev; Julia A. Lopatnikova; Alina A. Alshevskaya; Sergey V. Sennikov (Biomolecules)
Tumor necrosis factor (TNF) is a key immunoregulatory cytokine with a dual role in the host response to Mycobacterium tuberculosis. While essential for granuloma formation, macrophage activation, and containment of latent infection, TNF can also contribute to tissue damage and immune pathology. This review systematically analyzes over 300 peer-reviewed studies published between 1980 and 2024, highlighting the molecular and cellular mechanisms of TNF action in tuberculosis (TB). Particular attention is given to TNF receptor signaling pathways, the balance between protective and pathological immune responses, and the modulation of TNF activity during anti-TNF therapy in patients with autoimmune diseases. We discuss how different TNF inhibitors vary in their capacity to interfere with host defense mechanisms, with monoclonal antibodies carrying a higher reactivation risk than receptor-based agents. To enhance conceptual clarity, we provide newly developed schematic representations that integrate current knowledge on TNF-driven immune dynamics, including its interaction with other cytokines, effects on granuloma stability, and role in intracellular bacterial control. Understanding the pleiotropic functions of TNF in tuberculosis pathogenesis is crucial for developing safe immunomodulatory strategies and optimizing the clinical management of patients at risk of latent TB reactivation.